Religious Values and Character Education in The Drama “Celengan Tresna” - Waluyo, Budi (UIN Maulana Malik Ibrahim Malang, 2025)
This study departs from the growing academic interest in literature as a medium for moral and spiritual education, reflecting its potential to shape values through narrative and character portrayal. However, previous research has generally treated moral (character education) and religious values as separate domains, without examining their interrelation within a single literary work—especially in the context of modern Indonesian drama. The novelty of this study lies in its integrated analysis of both Islamic religious and character education values in the play Celengan Tresna, revealing how these values interact within the characters and narrative structure. This study aims to examine the Islamic values—such as sincerity (ikhlas), patience (ṣabr), honesty (ṣidq), and responsibility (amānah)—and character education reflected in Budi Waluyo’s drama Celengan Tresna. It employs a qualitative approach with content analysis method, referring to Glock and Stark’s theory of religiosity, which encompasses five dimensions: ideological, ritualistic, experiential, intellectual, and consequential. In analyzing the character education values, this study draws on the framework of Samani and Hariyanto, which outlines 26 education character values. The findings reveal that the play not only presents the religious values of its characters in dealing with life’s pressures, but also highlights various character values such as responsibility, hard work, care, honesty, and politeness, which are embedded within intrinsic elements such as characterization, dialogue, and plot. The study concludes that the play “Celengan Tresna” is not merely a narrative about its characters, but also serves as an effective medium for the internalization of moral and religious values. It also can be used as a practical medium for integrating religious and character education. Teachers may employ it to strengthen students’ moral and spiritual values—such as honesty, responsibility, and humility—through reflective literary learning. Penelitian ini berangkat dari meningkatnya perhatian akademik terhadap sastra sebagai media pendidikan moral dan spiritual, yang mencerminkan potensinya dalam membentuk nilai-nilai melalui narasi dan penggambaran tokoh. Namun, penelitian sebelumnya umumnya memperlakukan nilai moral (pendidikan karakter) dan nilai religius sebagai dua ranah yang terpisah, tanpa menelaah keterkaitan keduanya dalam satu karya sastra—terutama dalam konteks drama Indonesia modern. Kebaruan penelitian ini terletak pada analisis terpadu antara nilai-nilai religius Islam dan nilai-nilai pendidikan karakter dalam drama Celengan Tresna, yang mengungkap bagaimana kedua nilai tersebut berinteraksi melalui tokoh dan struktur naratif. Penelitian ini bertujuan untuk menelaah nilai-nilai Islam—seperti keikhlasan (ikhlas), kesabaran (ṣabr), kejujuran (ṣidq), dan tanggung jawab (amānah)—serta nilai-nilai pendidikan karakter yang tercermin dalam drama Celengan Tresna karya Budi Waluyo. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi, mengacu pada teori religiusitas Glock dan Stark yang mencakup lima dimensi: ideologis, ritualistik, pengalaman, intelektual, dan konsekuensial. Dalam menganalisis nilai-nilai pendidikan karakter, penelitian ini mengacu pada kerangka Samani dan Hariyanto yang memuat 26 nilai karakter pendidikan. Hasil penelitian menunjukkan bahwa drama ini tidak hanya menampilkan nilai-nilai religius Islam dalam cara tokohnya menghadapi tekanan hidup, tetapi juga menonjolkan berbagai nilai karakter seperti tanggung jawab, kerja keras, kepedulian, kejujuran, dan kesantunan yang terjalin dalam unsur intrinsik seperti penokohan, dialog, dan alur. Penelitian ini menyimpulkan bahwa Celengan Tresna bukan sekadar kisah tentang para tokohnya, tetapi juga berfungsi sebagai media efektif untuk internalisasi nilai-nilai moral dan religius Islam. Selain itu, drama ini dapat dimanfaatkan sebagai media praktis untuk mengintegrasikan pendidikan agama dan karakter. Guru dapat menggunakannya untuk memperkuat nilai-nilai moral dan spiritual siswa—seperti kejujuran, tanggung jawab, dan kerendahan hati—melalui pembelajaran sastra yang reflektif.